Quality of customer service in higher basic education (Revista Innova Educación, 2023)
The quality of services in education is fundamental to guarantee effective and satisfactory learning, promoting the integral development of students. The objective of this article was to diagnose the quality of customer service at the Unidad Educativa Particular “Internacional Puerto de Manta”.  The research had a mixed approach, integrating systematic, empirical and analytical processes. The SERVQUAL instrument was applied to 233 customers (internal and external) of the institution; the five dimensions were identified: “Tangible Elements, Reliability, Responsiveness, Security, Empathy”; with 22 items. The results indicated that the perception of customer service was positive in all dimensions. In conclusion, all the dimensions had a high score which implies user satisfaction; therefore, the institution demonstrates to have an educational planning updated and relevant to the advances and requirements of society. In addition, it has trained and knowledgeable personnel to carry out the teaching-learning process. It also has technological resources and materials that facilitate the efficient development of educational and administrative processes.
Keywords: customer service; quality; customer satisfaction; educational service